2012
DOI: 10.1111/j.1474-919x.2012.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐specific variance in sperm morphometry: a comparison between wild and domesticated Zebra FinchesTaeniopygia guttata

Abstract: The Zebra Finch Taeniopygia guttata is a model bird species for the experimental study of behavioural and evolutionary concepts in captivity and especially sexual selection. The validity of sexual selection studies of domesticated birds is of long‐standing concern as little is known about the influence of domestication on sexually selected traits. Most domesticated Zebra Finch populations are maintained under a strict breeding regime to avoid potential inbreeding. However, these breeding regimes may interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…On the other hand, using different recording procedures and having different people measure sperm morphology could decrease repeatability, despite statistical control for these factors. Our values for repeatability of morphology are comparable to those found in wild populations of other species (Lüpold et al, ; Cramer et al, ; Laskemoen et al, ;), and domestication and captivity seem to have minimal, if any, effects on sperm biology in zebra finches ( Taeniopygia guttata , Immler et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, using different recording procedures and having different people measure sperm morphology could decrease repeatability, despite statistical control for these factors. Our values for repeatability of morphology are comparable to those found in wild populations of other species (Lüpold et al, ; Cramer et al, ; Laskemoen et al, ;), and domestication and captivity seem to have minimal, if any, effects on sperm biology in zebra finches ( Taeniopygia guttata , Immler et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Further, the coefficients of variation for all the morphometric sperm head variables examined (length, width, area) were greater in the pure than in the hybrid partridges. At least in passerine birds, smaller intra-specific variation in sperm morphometry is related to an increased risk of sperm competition [67]. In addition, the VSL was higher in the more polygamous hybrid partridges [40].…”
Section: Sperm Velocity Variables and Their Importance In Competitionmentioning
confidence: 89%
“…Recent evidence suggests that head length evolves more slowly in response to sperm competition than other sperm traits (Rowe et al ), and it is known that head length tends to be a conserved trait in birds (Jamieson , Rowe et al ). However, there have also been several studies where head length has been found to diverge, both intraspecifically (Schmoll and Kleven , Immler et al ) and among closely related species (Omotoriogun et al ). This suggests that head length evolves separately from other sperm traits, although the reason for this separate evolution is unclear.…”
Section: Discussionmentioning
confidence: 99%